Leadership engagement among female undergraduates - Zuraidah Ali (Universiti Kebangsaan Malaysia, 2012)

(untitled)
The role of a student at university is all-encompassing. The experience exposes students to different soft skills from communicating and working together with friends across ethnics and nationalities, to organizing events for and with peers, lectures and the public. Despite this 'rich' surrounding promising personal development and recommendation for future employability, we still hear of undergraduates who are reluctant to assume leadership roles while at university. This study explores the potential factors that may be associated with reported lack of interest and participation in student leadership among female undergraduates. A survey research was conducted among female undergraduates residing at the on-campus accommodation. Results show that at least half of the female undergraduate cohort understand the importance of student leadership experience and have held at least one leadership position. Further, the study depicts some prevailing reasons for lack of involvement and nonparticipation in student leadership for the rest of the female undergraduate cohort.